An experimental and kinetic modeling study on the effects of molecular structure on oxidation of propanol isomers at engine-relevant condition in a variable pressure laminar flow reactor. (16th January 2023) - Zhang, Zhenyingnan; Li, Ang; Ma, Zheng; Zhu, Lei; Huang, Zhen
Graphical abstract: Highlights: A newly developed variable pressure laminar flow reactor was used for experiments. Speciation profiles of two propanol isomers were obtained at elevated pressure. Modified kinetic model of two propanol isomers for oxidation was developed. Effects of molecular structure of propanol isomers on oxidation have been analyzed. Abstract: Fuel combustion mechanism at different temperature and pressure range can be highly divers. In combustion process, many reactions are strongly pressure-dependent. Reactions that are important at low pressures may not be that important when pressure gets higher. Kinetic models developed and validated only at atmospheric conditions can have a large deviation when directly applied for higher pressures. Thus, experimental and kinetic studies at elevated to high pressures are essential for the understanding of fuel properties at engine-relevant conditions. However, speciation studies at such conditions are rare, which limits prediction accuracy of kinetic models. Propanol is the smallest alcohol that has isomers, and can be produced via carbon–neutral routes. Study on propanol can reveal the effect of isomerization and facilitate kinetic studies of larger alcohols. In present work, experiments have been carried out at elevated pressure in a variable pressure laminar flow reactor. Speciation data has been measured and compared. Moreover, a previous kinetic model has been modified and validated to improve prediction accuracy at elevated pressure and has been used for further kinetic analysis. The structural difference between two isomers affects their oxidation pathways and intermediate species. The position of hydroxyl moiety and bond dissociation energy of α -H have led to different oxidation properties of these two isomers. Through present work, the effect of molecular structure on oxidation properties of propanol isomers at elevated pressure have been studied. Speciation database of propanol isomers at elevated pressure has been enriched, and prediction accuracy of a previous model at present conditions has been improved.